2019
DOI: 10.1007/s12178-019-09543-9
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic Ossification in Hip Arthroscopy: an Updated Review

Abstract: Purpose of Review Heterotopic ossification (HO) in hip arthroscopy is a common post-operative complication. This review was undertaken to provide an update (2014 present) on the current literature regarding HO in hip arthroscopy. Recent Findings Risk factors for HO post-hip arthroscopy include male gender, mixed impingement, picture, and the size of CAM resection. HO prophylaxis with NSAIDs has been proven to decrease the rate of HO post-hip arthroscopy; however, there is inherent risk to long-standing NSAIDs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 29 publications
0
40
0
Order By: Relevance
“…Heterotopic ossification prophylaxis with nonsteroidal anti-inflammatory drugs was recommended for 2 to 3 weeks. 24,50…”
Section: Methodsmentioning
confidence: 99%
“…Heterotopic ossification prophylaxis with nonsteroidal anti-inflammatory drugs was recommended for 2 to 3 weeks. 24,50…”
Section: Methodsmentioning
confidence: 99%
“…Most HO is asymptomatic and only requires excision in rare settings. 3 In addition, although the PRECISION (Prospective Randomized Evaluation of Celecoxib Integrated Safety versus Ibuprofen or Naproxen) trial showed noninferiority of celecoxib to naproxen, 4 Celecoxib has fewer gastrointestinal effects than naproxen, and is (probably) just as safe from a cardiovascular standpoint, 4 but that is different than saying celecoxib is a benign drug. 6 Does prophylactic treatment justify the risks?…”
Section: See Related Article On Page 453mentioning
confidence: 99%
“…Heterotopic ossification (HO) is a common complication following hip arthroscopy with an incidence of up to 44% [1,2]. Reported risk factors include male gender, femoral neck osteochondroplasty, and unrepaired capsulotomy [1][2][3][4]. Current treatments range from nonoperative management of asymptomatic lesions, ultrasound guided lavage for a small symptomatic HO lesion, and revision surgery for excision of painful lesions [5].…”
Section: Introductionmentioning
confidence: 99%